Pengaruh Pengembangan Wisata Desa Mandeh Terhadap Pendapatan UMKM Disekitarnya Dengan Potensi Wisata Sebagai Variabel Intervening - Al Zahra, Anatha Fatimah; Artadita, Sherly (eProceedings of Management, 2024)
The economics and revenue of the community can be enhanced by tourism, particularly for micro, small, and mediumsized businesses (MSMEs) located near popular tourist destinations. Called the 'Bali' of West Sumatra, MandehVillage tourist is currently a popular tourist among the local people. Mandeh Village is a recently established touristspot. The purpose of this study is to investigate how the growth of tourism in Mandeh Village affects the revenue ofnearby MSMEs, with a focus on the potential for tourism. This study employed a quantitative approach using adescriptive analytic methodology. A total of 100 MSMEs in the Mandeh tourism area were the population used in thestudy. The study's findings demonstrate that Mandeh Village's tourism development has a positive and significantimpact on MSME income, as does tourism potential. Additionally, Mandeh Village's tourism development has apositive and significant impact on local MSME income, which is mediated by tourism potential..Keywords-tourism development, MSME income, tourism potential